2019
DOI: 10.1002/admi.201900718
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐Polarized Electronic Transport through Ferromagnet/Organic–Inorganic Hybrid Perovskite Spinterfaces at Room Temperature

Abstract: COMMUNICATION 1900718 (1 of 7)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Indeed, it has been previously shown that the interfacial properties differ from the bulk Ni film because of the changes of the magnetization, coercivity, and magnetic moment. [17] As it has been theoretically studied, the electronic structure of MAPbI 3 is mainly decided by − PbI 3 . If i-DOS are spin-dependent, photoexcited electrons near the band-edge of the valence band should be partially polarized due to the orbit hybridization/mixing effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it has been previously shown that the interfacial properties differ from the bulk Ni film because of the changes of the magnetization, coercivity, and magnetic moment. [17] As it has been theoretically studied, the electronic structure of MAPbI 3 is mainly decided by − PbI 3 . If i-DOS are spin-dependent, photoexcited electrons near the band-edge of the valence band should be partially polarized due to the orbit hybridization/mixing effect.…”
Section: Discussionmentioning
confidence: 99%
“…[13,14] By far, spin related phenomena for OIHPs have been studied via measurements of magnetic field effects (MFEs) and spin-polarized electronic transport. [15][16][17][18][19] The formation of the ferromagnet/ perovskite spinterface such as Ni/MAPbI 3−x Cl x and Co/ MAPbI 3−x Cl x are known to have remarkable impact on magnetoresistance (MR) and magnetodielectric responses. [17,20] The hybrid interface can be also useful for generating spin-hall and inverse spin-hall effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following those two earliest studies, follow-up works have demonstrated various spin phenomena across different perovskite systems. Several works to be highlighted include experimental demonstration of quantum spin-beating [153,154], spin-selective optical Stark effect [155,156], Rashba effect [143,157], and perovskite based spin-valves [149,158,159].…”
Section: Please Cite This Article As Doi: 101063/50031821mentioning
confidence: 99%
“…Moreover, halide perovskites can be solution processed at low temperatures, which significantly reduces their fabrication cost and complexity 4 . These advantages have led to the emergence of a variety of novel perovskite-based devices in the past decade 5 , 6 , such as solar cells (SCs) 7 – 10 , light-emitting diodes (LEDs) 11 14 , lasers 15 17 , photodetectors (PDs) 18 20 , sensors 21 , 22 , catalyst electrodes 23 25 , field-effect transistors 26 , 27 , fuel cells 28 , 29 , memory 30 , 31 and spintronic devices 32 , 33 . However, halide perovskites are prone to phase changes and compositional degradation in the ambient environment.…”
Section: Introductionmentioning
confidence: 99%